Multimodal Management and Triple Nerve Transfer for Optimal Recovery of Shoulder Function Following Neonatal Brachial Plexus Palsy: A Case Report. Issue 5 (4th March 2019) - Osorio, Marisa; Lewis, Sarah; Tse, Raymond
Abstract : Neonatal brachial plexus palsy is a complex disorder that requires evaluation of the primary nerve injury and associated sequelae. There is no standardized approach to management, and many treatment options are available. We present a case of Erb palsy with a unique multidisciplinary approach to nonsurgical and surgical management. Inherent in the case is the complexity of decision‐making, and we review the literature on treatment options and the rationale for the approach, which resulted in near normal functional recovery.